Fostering social innovation and building adaptive capacity for dengue control in Cambodia: a case study - Pierre Echaubard; Chea Thy; Soun Sokha; Set Srun; Claudia Nieto-Sanchez; Koen Peters Grietens; Noel R. Juban; Jana Mier-Alpano; Sucelle Deacosta; Mojgan Sami; Leo Braack; Bernadette Ramirez; et al. (BMC, 2020)
Abstract Background The social-ecological systems theory, with its unique conception of resilience (social-ecological systems & resilience, SESR), provides an operational framework that currently best meets the need for integration and adaptive governance as encouraged by the Sustainable Development Goals. SESR accounts for the complex dynamics of social-ecological systems and operationalizes transdisciplinarity by focusing on community engagement, value co-creation, decentralized leadership and social innovation. Targeting Social Innovation (SI) in the context of implementation research for vector-borne diseases (VBD) control offers a low-cost strategy to contribute to lasting and contextualized community engagement in disease control and health development in low and middle income countries of the global south. In this article we describe the processes of community engagement and transdisciplinary collaboration underpinning community-based dengue management in rural primary schools and households in two districts in Cambodia. Methods Multiple student-led and community-based interventions have been implemented focusing on empowering education, communication for behavioral change and participatory epidemiology mapping in order to engage Cambodian communities in dengue control. We describe in particular the significance of the participatory processes that have contributed to the design of SI products that emerged following iterative consultations with community stakeholders to address the dengue problem. Results The SI products that emerged following our interaction with community members are 1) adult mosquito traps made locally from solid waste collections, 2) revised dengue curriculum with hands-on activities for transformative learning, 3) guppy distribution systems led by community members, 4) co-design of dengue prevention communication material by students and community members, 5) community mapping. Conclusions The initiative described in this article put in motion processes of community engagement towards creating ownership of dengue control interventions tools by community stakeholders, including school children. While the project is ongoing, the project's interventions so far implemented have contributed to the emergence of culturally relevant SI products and provided initial clues regarding 1) the conditions allowing SI to emerge, 2) specific mechanisms by which it happens and 3) how external parties can facilitate SI emergence. Overall there seems to be a strong argument to be made in supporting SI as a desirable outcome of project implementation towards building adaptive capacity and resilience and to use the protocol supporting this project implementation as an operational guiding document for other VBD adaptive management in the region.